Development and validation of an instrument to assess future orientation and resilience in adolescence. (25th June 2016) - Di Maggio, Ilaria; Ginevra, Maria Cristina; Nota, Laura; Soresi, Salvatore
ABSTRACT: The study is aimed at providing the development and initial validation of the Design My Future (DMF), which may be administered in career counseling and research activities to assess adolescents' future orientation and resilience. Two studies with two independent samples of Italian adolescents were conducted to examine psychometric requisites of DMF. Specifically, in the first study, after developing items and examined the content validity, the factorial structure, reliability and discriminant validity of the DMF were tested. In the second study, the measurement invariance across gender, conducing a sequence of nested CFA models, was evaluated. Results showed good psychometric support for the instrument with Italian adolescents.